EFEKTIFITAS PENGGUNAAN MEDIA BOLD LINE BOOK UNTUK MENINGKATKAN KEMAMPUAN MENULIS KALIMAT LATIN BAGI ANAK LOW VISION - Ledy Wirda Maysyarah (Jurnal Penelitian Pendidikan Khusus, 2013)
This research background by the problems that researchers find in SDN 18 Limau Manis Padang, a child is a class III Low vision SDN semester are having trouble viewing line of the book, it was originally seen when researchers looked at the implementation of ongoing writing Latin in class III SDN 18, after apparently observed the child have difficulty in seeing the line of writing the book so hard to read. This research Single Subject Research approach, the ABA design and data analysis techniques using visual analysis chart. The results of this study indicate that the media Bold Line Book effective in improving writing skills in teaching latin writing for children class III Low Vision SDN 18 Limau Manis Padang. Observations made with the first three sessions, the session before being given intervention baseline (A1) performed seven times of observation, Second, the intervention sessions (B) by using the media Bold Line Book survey is performed ten times, Third session baseline (A2) is done five times of observation. Based on these results it can be concluded media Bold Line Book effective in improving writing skills for young latin class III Low Vision SDN 18 Limau Manis Padang. Suggested the teachers should be able to use the media Bold Line Book the wrote the latin low vision in children.